WO3 and ZnO-doped SnO2 ceramics as insulating material - Margionte, M. A. L.; Simoes, A. Z.; Riccardi, C. S.; Filho, F. M.; Ries, A.; Perazolli, L.; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
SnO2 ceramics doped with ZnO and WO3 were prepared by mixed oxide method. The effect of ZnO and WO3 additives could be explained by the substitution of Sn4+ by Zn2+ and W6+. The addition of WO3 inhibits the grain growth due to the segregation of SnZnWO8 and ZnWO6 at the grain boundaries without strong influence on the densification process. The electrical characterization (log E x log J) shows that the ternary system SnO2-ZnO-WO3 exhibits a very high resistivity of around 10(14) Omega M. Independently of the WO3 concentration, the electrical conductivity of the Sn02-ZnO-WO3 system is always lower than that of the undoped tin dioxide. (C) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: sintering; insulators; tin dioxide